Synergistic effects of foliar and soil inoculation with plant growth-promoting bacteria: enhancing sugarcane metabolism, productivity, and rhizosphere modulation - Fonseca, Mariley de Cássia da [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Sugarcane (Saccharum spp.) is a crop of great importance, playing a strategic role in the production of sugar, bioenergy, and biofuels. However, its intensive cultivation, particularly in tropical environments, faces challenges related to low nitrogen (N) use efficiency, high nutritional demand, and environmental impacts resulting from the application of synthetic fertilizers. In this context, the inoculation with plant growth-promoting bacteria (PGPB) has emerged as a promising alternative to increase productive efficiency, reduce fertilizer losses, and mitigate the adverse effects of environmental stress. This study uniquely investigated the effects of inoculation with Azospirillum brasilense (Ab), applied via foliar spraying, and Nitrospirillum amazonense (Na), applied to the soil, either individually or in consortium, on the physiological, nutritional, biochemical, and productive aspects of sugarcane. The experiments were conducted under greenhouse conditions and validated in the field. Results demonstrated that inoculation, particularly with Ab and the consortium (Ab+Na), enhanced the nutritional status of plants, especially by increasing N content. These improvements were reflected in favorable biochemical responses, such as reduced oxidative stress and enhanced photosynthetic parameters, water-use efficiency, and carboxylation efficiency, ultimately leading to higher stalk and sugar yields. In addition, inoculation modulated N dynamics within the soil–plant system by increasing N-fertilizer recovery, reducing losses through nitrification and denitrification, and enhancing the abundance of the nifH gene associated with biological N fixation. Changes in microbial community composition were also observed, with emphasis on the PGPB consortium, which promoted a more uniform structure functionally associated with improved nutrient-use efficiency. The findings of this study reinforce the potential of combined foliar (Ab) and soil (Na) inoculation as a sustainable strategy to intensify sugarcane production, promoting agronomic gains while contributing to reduced environmental impacts. The integration of physiological, nutritional, and microbial responses highlights the importance of biological management in the transition toward more efficient and resilient agricultural systems.

A cana-de-açúcar (Saccharum spp.) é uma cultura de grande importância, com papel estratégico na produção de açúcar, bioenergia e biocombustíveis. No entanto, seu cultivo intensivo, especialmente em ambientes tropicais, enfrenta desafios relacionados à baixa eficiência no uso de nitrogênio (N), elevada demanda nutricional e impactos ambientais decorrentes da aplicação de fertilizantes sintéticos. Nesse contexto, a adoção da inoculação com bactérias promotoras de crescimento de plantas (BPCP), tem emergido como alternativa promissora para aumentar a eficiência produtiva, reduzir perdas de fertilizantes e mitigar os efeitos adversos do estresse ambiental. Este trabalho investigou, de forma inédita, os efeitos da inoculação com Azospirillum brasilense (Ab), via foliar, e Nitrospirillum amazonense (Na), via solo, aplicados isoladamente ou em consórcio, sobre aspectos fisiológicos, nutricionais, bioquímicos e produtivos da cana-de-açúcar. Os estudos foram conduzidos em casa de vegetação e validados em campo. Os resultados demonstraram que a inoculação, especialmente com Ab e o consórcio (Ab+Na), promoveu melhorias no estado nutricional, com destaque para o aumento do teor de N nas plantas. Tais incrementos refletiram-se em respostas bioquímicas favoráveis, como a redução do estresse oxidativo e o aprimoramento de parâmetros fotossintéticos, eficiência de uso da água e da carboxilação, culminando em elevação da produtividade de colmos e de açúcar. Adicionalmente, a inoculação modulou a dinâmica do N no sistema solo-planta, aumentando a recuperação do N-fertilizante, reduzindo perdas por processos de nitrificação e desnitrificação e elevando a abundância do gene nifH, associado à fixação biológica de N. Alterações na composição da comunidade microbiana também foram observadas, com destaque para o consórcio de BPCP, que favoreceu uma estrutura microbiana mais uniforme e funcionalmente associada à melhoria da eficiência do uso de nutrientes. Os achados deste estudo reforçam o potencial da inoculação combinada via foliar (Ab) e via solo (Na) como estratégia sustentável para intensificação da produção de cana-de-açúcar, promovendo ganhos agronômicos e contribuindo para a redução de impactos ambientais. A integração de respostas fisiológicas, nutricionais e microbianas evidencia a importância do manejo biológico na transição para sistemas agrícolas mais eficientes e resilientes.
Efeitos sinérgicos da inoculação foliar e do solo com bactérias promotoras de crescimento de plantas: aprimorando o metabolismo, a produtividade e a modulação da rizosfera da cana-de-açúcar
Keywords: Nitrogen cycle; Diazotrophic bacteria; Photosynthesis; Organic acids; Oxidative stress